INFLUENCE OF SUBSTITUTING WHEAT STRAW WITH CORNCOBS IN FATTENING RATIONS FOR GROWTH RATE AND NUTRIENT DIGESTIBILITY IN BUFFALO CALVES - M. I. Anjum; M. Afzal (Journal of Animal and Plant Sciences, 2015)
Nine Nili-Ravi buffalo calves age between 10-12 months and average body weights 160±3.30 kg were randomly divided into three groups (3 animals in each). Three iso-nitrogenous (12% CP) and iso-caloric (68% TDN) total mixed diets were formulated as: Diet A contained 75% DM from concentrate +25% DM from wheat straw; diet B had 75% DM from concentrate +13% DM from wheat straw +12% DM from corncobs while, diet C consisted of 75% DM from concentrate +25% DM from corncobs. All calves were offered 7-8 kg/day of available green fodders (oats, maize and millet). The study lasted for 105 days (March to July). Growth trial was followed by a five days digestibility trial. Results revealed no-significant difference in the intake of dry matter (DM) among all groups, however, the total body weight gain or average daily weight gain and feed conversion ratio (FCR) were better (P<0.05) in calves of group C compared to group A, however group A and C were not different (P>0.05) from group B. Similar pattern was found in digestibility of DM, crude protein (CP) and crude fibre (CF) among the groups. However, digestibility of NDF and ADF was different (P<0.05) among all groups with maximum in group C and minimum in group A. Similarly, N retention was significantly (P<0.05) higher in group C followed by groups B and A. Feed cost per kg weight gain of group C was 31.32% and 25.00% less than calves in groups A and B, respectively. It may be concluded that corncobs can beneficially substitute with wheat straw for fattening of buffalo calves.
Keywords: Buffalo calves; Growth rate; Digestibility; Wheat straw and Corncobs